Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material as well as preparation method and application thereof

Through the design of Bi-Bi2Sn2O7/g-C3N4 composite photocatalytic material, the existing performance problems of existing photocatalysts in the photosynthesis of H2O2 are solved, and the effect of significantly improving photocatalytic activity and cyclic stability is achieved.

CN119456015AActive Publication Date: 2025-02-18YANCHENG INST OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411828156.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

During the photosynthesis of H2O2, existing photocatalysts have narrow spectral response range, easy recombination of photogenerated charges, poor electron conduction ability, and aggregation and adhesion problems, resulting in low specific surface area, limiting their promotion and application.

Method used

Bi-Bi2Sn2O7/g-C3N4 composite photocatalytic material is used to combine g-C3N4 with Bi-Bi2Sn2O7 to adjust the structure and performance of the material, and improve its photocatalytic activity and cyclic stability.

Benefits of technology

The activity and cycle stability of photocatalytic H2O2 production were significantly improved. Under visible light and simulated sunlight irradiation, the H2O2 generation rate of Bi-Bi2Sn2O7/g-C3N4 composites was increased by 8.5 times and 7.5 times respectively, and maintained efficiently. Cyclic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119456015A_ABST
    Figure CN119456015A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photocatalytic H2O2 production, in particular to a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing melamine, cyanuric acid and water, and sequentially drying and calcining to obtain a g-C3N4 photocatalytic material; the preparation method comprises the following steps: dispersing a g-C3N4 photocatalytic material in water to obtain a photocatalytic material solution; mixing bismuth nitrate, polyvinylpyrrolidone and a D-mannitol solution to obtain a bismuth nitrate-containing solution; and mixing the photocatalytic material solution, a bismuth nitrate-containing solution and a potassium selenate solution, carrying out a hydrothermal reaction, and drying to obtain the Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material. The preparation process is simple, easy to control and low in production cost, and the prepared Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material has the characteristics of high activity, good selectivity and excellent cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalytic H2O2 production, and in particular to a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material and a preparation method and application thereof. Background Art

[0002] Hydrogen peroxide (H2O2) is an important and widely used environmentally friendly and harmless oxidant. The only byproduct of its oxidation reaction is water. Hydrogen peroxide is also an ideal energy storage material with high energy density. Compared with hydrogen, it is easier to store and transport. In short, hydrogen peroxide is widely used in organic synthesis, environmental protection and other fields as a chemical product, and plays an important role in chemical production. The current industrial method for producing hydrogen peroxide is the anthraquinone (AQ) method, or directly mixing H2 with O2. However, the former requires high temperature and high pressure, has high energy consumption, and also produces polluting waste, while the latter has a great explosion hazard, and the reaction also requires the use of precious metals as co-catalysts. In contrast, photosynthetic H2O2 is the oxidation and reduction of water and oxygen into H2O2 using photocatalysts under sunlight. Solar energy is inexhaustible, and almost no waste is produced during the photocatalytic process. Therefore, photosynthetic H2O2 is considered to be a very promising green way to synthesize H2O2. At present, the research on photosynthetic H2O2 system is still in its preliminary stage, and the development of new, efficient, stable and cheap photocatalysts is the research focus of scientists.

[0003] Polymer carbon nitride is a two-dimensional layered material with a graphite-like structure mainly composed of two elements, carbon and nitrogen. It has unique electronic structure and optical properties, excellent chemical stability, easy structural regulation, non-toxicity and low cost, and has become a research hotspot in the current field of photocatalysis. In recent years, the use of polymer carbon nitride for photosynthesis of H2O2 has attracted widespread attention worldwide. However, carbon nitride has a narrow spectral response range, photogenerated charges are prone to recombination, and its electron conductivity is poor. In addition, it aggregates and adheres during the synthesis process, resulting in a low specific surface area. These problems have seriously restricted the promotion and application of carbon nitride photocatalysts. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material and its preparation method and application. The preparation process of the present invention is simple, easy to control and has low production cost. The prepared Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material has the characteristics of high activity, good selectivity and excellent cycle stability.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material, comprising the following steps:

[0007] 1) mixing melamine, cyanuric acid and water, and then drying and calcining in sequence to obtain a g-C3N4 photocatalytic material;

[0008] 2) dispersing the g-C3N4 photocatalytic material obtained in step 1) in water to obtain a photocatalytic material solution;

[0009] Mixing bismuth nitrate, polyvinyl pyrrolidone and D-mannitol solution to obtain a bismuth nitrate-containing solution;

[0010] 3) The photocatalytic material solution obtained in step 2), the bismuth nitrate solution and the potassium selenate solution are mixed, the pH value is adjusted to 10.0-12.0, and then a hydrothermal reaction is carried out. After drying, a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material is obtained.

[0011] Preferably, in step 1), the mass ratio of melamine, cyanuric acid and water is 1:1:40.

[0012] Preferably, the drying conditions in step 1) include: temperature of 60° C. and time of 12 h;

[0013] The calcination conditions include: heating to 500-600° C. at a heating rate of 5-10° C. / min and keeping the temperature for 1-3 hours.

[0014] Preferably, in step 2), the mass ratio of the g-C3N4 photocatalytic material to water is 1 to 3:20.

[0015] Preferably, in step 2), the volume ratio of the mass of bismuth nitrate, the mass of polyvinyl pyrrolidone and the D-mannitol solution is 0.48 g:0.4 g:30 mL;

[0016] The concentration of the D-mannitol solution is 0.5 mol / L.

[0017] Preferably, in step 3), the volume ratio of the photocatalytic material solution, the bismuth nitrate-containing solution and the potassium selenate solution is 4:6:1;

[0018] The concentration of the potassium selenate solution is 0.06 g / mL.

[0019] Preferably, the conditions of the hydrothermal reaction in step 3) include: a temperature of 160 to 200° C. and a time of 12 to 24 hours;

[0020] The drying temperature is 80°C.

[0021] The present invention provides a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material prepared by the preparation method described in the above technical solution.

[0022] The present invention also provides the use of the Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material described in the above technical solution in photocatalytic production of H2O2.

[0023] Preferably, the application includes: photocatalytic production of H2O2 under visible light or sunlight.

[0024] Beneficial effects of the present invention:

[0025] (1) The present invention disperses melamine and cyanuric acid in a mixed solution of water and ethanol, stirs and mixes evenly, calcines and anneals in a closed tube furnace after drying, and cools naturally to obtain thinner g-C3N4 as a carrier. Subsequently, g-C3N4 is dispersed in deionized water, bismuth nitrate, PVP and mannitol are added as A solution, and potassium selenate is dissolved in deionized water as B solution. Then, the B solution is slowly added dropwise to the A solution and stirred continuously, mixed evenly, and the pH of the solution is adjusted with KOH. Finally, it is transferred to a polytetrafluoroethylene high-pressure reactor for hydrothermal heating, and then cooled to room temperature to obtain a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material. The method of the present invention has a simple process, a short preparation time, and low energy consumption. The prepared Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material has a rich pore structure and a large specific surface area.

[0026] (2) The photocatalytic performance of the Bi-Bi2Sn2O7 / g-C3N4 composite material prepared by the present invention was evaluated by photocatalytic H2O2 production in an oxygen atmosphere. The test results showed that under visible light irradiation, the Bi-Bi2Sn2O7 / g-C3N4 composite material produced a cumulative H2O2 of 780.5 μmol L-1 in 5 hours. -1 The average rate was 156.1 μmol L -1 h -1 Under simulated sunlight, the Bi-Bi2Sn2O7 / g-C3N4 composite material produced a cumulative H2O2 of 955.5 μmol L-1 within 5 hours. -1 The average rate was 191.1 μmol L -1 h -1 The above photocatalytic activity is 8.5 times and 7.5 times higher than that of pure g-C3N4 under visible light and simulated sunlight, respectively. In addition, Bi-Bi2Sn2O7 / g-C3N4 still has high photocatalytic activity after multiple cycles.

[0027] (3) The Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material prepared by the present invention can effectively enhance the activity and cycle stability of photocatalytic H2O2 production, and has broad development prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.

[0029] Figure 1 is an X-ray diffraction (XRD) pattern of the Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material prepared in Example 1 of the present invention;

[0030] Figure 2 is a scanning electron microscope (SEM) image of the Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material prepared in Example 2 of the present invention;

[0031] Figure 3 Schematic diagram of the activity of Bi-Bi2Sn2O7, g-C3N4 and Bi-Bi2Sn2O7 / g-C3N4 (X=1, 2, 3) composite photocatalytic materials for producing H2O2 prepared in Example 1 of the present invention;

[0032] Figure 4 Schematic diagram of the activity of the Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material in producing H2O2 under different external conditions prepared in Example 2 of the present invention;

[0033] Figure 5 Schematic diagram of the activity of Bi-Bi2Sn2O7 in producing H2O2 under different external conditions prepared in Example 2 of the present invention;

[0034] Figure 6 Schematic diagram of the activity of g-C3N4 in producing H2O2 under different external conditions prepared in Example 2 of the present invention;

[0035] Figure 7 It is a schematic diagram of the cyclic stability of the Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material produced under light irradiation;

[0036] Figure 8 It is a schematic diagram of the cyclic stability of g-C3N4 produced by Example 2 of the present invention in producing H2O2 under light;

[0037] Fig. 9 It is a schematic diagram of the cyclic stability of the Bi-Bi2Sn2O7 material prepared in Example 2 of the present invention in producing H2O2 under light. DETAILED DESCRIPTION

[0038] The present invention provides a method for preparing a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material, comprising the following steps:

[0039] 1) mixing melamine, cyanuric acid and water, and then drying and calcining in sequence to obtain a g-C3N4 photocatalytic material;

[0040] 2) dispersing the g-C3N4 photocatalytic material obtained in step 1) in water to obtain a photocatalytic material solution;

[0041] Mixing bismuth nitrate, polyvinyl pyrrolidone and D-mannitol solution to obtain a bismuth nitrate-containing solution;

[0042] 3) The photocatalytic material solution obtained in step 2), the bismuth nitrate solution and the potassium selenate solution are mixed, the pH value is adjusted to 10.0-12.0, and then a hydrothermal reaction is carried out. After drying, a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material is obtained.

[0043] The present invention mixes melamine, cyanuric acid and water, and then dries and calcines in sequence to obtain a g-C3N4 photocatalytic material. In the present invention, the mass ratio of melamine, cyanuric acid and water is preferably 1:1:40. In the present invention, the drying conditions preferably include: a temperature of 60°C and a time of 12 hours. In the present invention, the calcination conditions preferably include: heating to 500-600°C at a heating rate of 5-10°C / min and keeping warm for 1-3 hours.

[0044] The present invention disperses the obtained g-C3N4 photocatalytic material in water to obtain a photocatalytic material solution; bismuth nitrate, polyvinyl pyrrolidone and D-mannitol solution are mixed to obtain a bismuth nitrate-containing solution. In the present invention, the mass ratio of the g-C3N4 photocatalytic material and water is preferably 1 to 3:20. In the present invention, the mass ratio of the bismuth nitrate, the mass of polyvinyl pyrrolidone and the volume ratio of the D-mannitol solution is preferably 0.48g:0.4g:30mL. In the present invention, the concentration of the D-mannitol solution is preferably 0.5mol / L.

[0045] The present invention mixes the obtained photocatalytic material solution, bismuth nitrate-containing solution and potassium selenate solution, adjusts the pH value to 10.0-12.0, performs a hydrothermal reaction, and obtains a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material after drying. In the present invention, the volume ratio of the photocatalytic material solution, the bismuth nitrate-containing solution and the potassium selenate solution is preferably 4:6:1. In the present invention, the concentration of the potassium selenate solution is preferably 0.06g / mL. In the present invention, the conditions of the hydrothermal reaction preferably include: a temperature of 160-200°C and a time of 12-24h. In the present invention, the drying temperature is preferably 80°C.

[0046] The present invention provides a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material prepared by the preparation method described in the above technical solution.

[0047] The present invention also provides the use of the Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material described in the above technical solution in photocatalytic production of H2O2. In the present invention, the use preferably includes: photocatalytic production of H2O2 under visible light or sunlight.

[0048] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0049] Example 1

[0050] A method for preparing a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material, comprising the following steps:

[0051] S1. Disperse 5.0 g of melamine and 5.0 g of cyanuric acid into 200 ml of deionized water and stir to mix well.

[0052] S2. Transfer the thoroughly mixed melamine and cyanuric acid solution to a vacuum drying oven, keep it at 60°C for 12 hours, and then cool it to room temperature after drying; then transfer the obtained melamine and cyanuric acid composite precursor to a closed tubular furnace, heat it to 550°C at a heating rate of 5°C / min, and keep it for 2 hours; cool it naturally to obtain a g-C3N4 photocatalytic material with a thinner nanosheet layer.

[0053] S3. Add 0.48g Bi(NO3)3-5H2O and 0.4g PVP to 30ml 0.5M D-mannitol solution, called solution A. Subsequently, dissolve 0.3g K2SnO3-3H2O in 5ml deionized water to obtain solution B. Slowly drop solution B into solution A, stir ultrasonically, and mix evenly. Adjust pH to 10.0 with 2M KOH solution. Finally, transfer the mixed solution to a 100ml high-pressure reactor and keep it at 180℃ for 24h. After the reaction is completed, cool naturally to room temperature, wash by centrifugation, and dry the mixture at 80℃ to obtain Bi-Bi2Sn2O7 photocatalytic material, named B-BSO.

[0054] S4. Take 1g of g-C3N4 nanosheets and disperse them in 20ml of deionized water. Add 0.48g of Bi(NO3)3-5H2O and 0.4g of PVP to 30ml of 0.5M D-mannitol solution, which is called solution A. Subsequently, dissolve 0.3g of K2SnO3-3H2O in 5ml of deionized water to obtain solution B. Slowly drop solution B into solution A, stir ultrasonically, and mix evenly. Adjust the pH to 10.0 with 2M KOH solution. Finally, transfer the mixed solution to a 100ml high-pressure reactor and keep it at 180°C for 24h. After the reaction is completed, cool it naturally to room temperature, wash it by centrifugation, and dry the mixture at 80°C to obtain a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material, named B-BSO / g-CN-1.

[0055] Example 2

[0056] A method for preparing a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material, comprising the following steps:

[0057] S1. Disperse 5.0 g of melamine and 5.0 g of cyanuric acid into 200 ml of deionized water and stir to mix well.

[0058] S2. Transfer the thoroughly mixed melamine and cyanuric acid solution to a vacuum drying oven, keep it at 60°C for 12 hours, and then cool it to room temperature after drying; then transfer the obtained melamine and cyanuric acid composite precursor to a closed tubular furnace, heat it to 550°C at a heating rate of 5°C / min, and keep it for 2 hours; cool it naturally to obtain a g-C3N4 photocatalytic material with a thinner nanosheet layer.

[0059] S3. Add 0.48g Bi(NO3)3-5H2O and 0.4g PVP to 30ml 0.5M D-mannitol solution, called solution A. Subsequently, dissolve 0.3g K2SnO3-3H2O in 5ml deionized water to obtain solution B. Slowly drop solution B into solution A, stir ultrasonically, and mix evenly. Adjust pH to 10.0 with 2M KOH solution. Finally, transfer the mixed solution to a 100ml high-pressure reactor and keep it at 180℃ for 24h. After the reaction is completed, cool naturally to room temperature, wash by centrifugation, and dry the mixture at 80℃ to obtain Bi-Bi2Sn2O7 photocatalytic material, named B-BSO.

[0060] S4, take 2g of g-C3N4 nanosheets and disperse them in 20ml of deionized water, add 0.48g of Bi(NO3)3-5H2O and 0.4g of PVP to 30ml of 0.5M D-mannitol solution, called A solution. Subsequently, 0.3g of K2SnO3-3H2O was dissolved in 5ml of deionized water to obtain B solution. Slowly drop B solution into A solution, stir ultrasonically, and mix evenly. Adjust pH to 10.0 with 2M KOH solution. Finally, transfer the mixed solution to a 100ml high-pressure reactor and keep it at 180℃ for 24h. After the reaction is completed, cool it naturally to room temperature, wash it by centrifugation, and dry the mixture at 80℃ to obtain Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material, named B-BSO / g-CN-2.

[0061] Example 3

[0062] A method for preparing a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material, comprising the following steps:

[0063] S1. Disperse 5.0 g of melamine and 5.0 g of cyanuric acid into 200 ml of deionized water and stir to mix well.

[0064] S2. Transfer the thoroughly mixed melamine and cyanuric acid solution to a vacuum drying oven, keep it at 60°C for 12 hours, and then cool it to room temperature after drying; then transfer the obtained melamine and cyanuric acid composite precursor to a closed tubular furnace, heat it to 550°C at a heating rate of 5°C / min, and keep it for 2 hours; cool it naturally to obtain a g-C3N4 photocatalytic material with a thinner nanosheet layer.

[0065] S4. Add 0.48g Bi(NO3)3-5H2O and 0.4g PVP to 30ml 0.5M D-mannitol solution, called solution A. Subsequently, dissolve 0.3g K2SnO3-3H2O in 5ml deionized water to obtain solution B. Slowly drop solution B into solution A, stir ultrasonically, and mix evenly. Adjust pH to 10.0 with 2M KOH solution. Finally, transfer the mixed solution to a 100ml high-pressure reactor and keep it at 180℃ for 24h. After the reaction is completed, cool naturally to room temperature, centrifuge and wash, and dry the mixture at 80℃ to obtain Bi-Bi2Sn2O7 photocatalytic material, named B-BSO.

[0066] S4, take 3g of g-C3N4 nanosheets and disperse them in 20ml of deionized water, add 0.48g of Bi(NO3)3-5H2O and 0.4g of PVP to 30ml of 0.5M D-mannitol solution, called A solution. Subsequently, 0.3g of K2SnO3-3H2O was dissolved in 5ml of deionized water to obtain B solution. Slowly drop B solution into A solution, stir ultrasonically, and mix evenly. Adjust pH to 10.0 with 2M KOH solution. Finally, transfer the mixed solution to a 100ml high-pressure reactor and keep it at 180℃ for 24h. After the reaction is completed, cool it naturally to room temperature, wash it by centrifugation, and dry the mixture at 80℃ to obtain Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material, named B-BSO / g-CN-3.

[0067] Performance Test:

[0068] 1. Use XRD instrument to analyze the phase structure of the Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material prepared in Examples 1-3.

[0069] Figure 1 The XRD spectra of Bi-Bi2Sn2O7, g-C3N4 and Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic materials prepared in Examples 1-3 are used to characterize the crystal structures of different materials. Figure 1 As shown in the figure, the characteristic peaks at 13.2° and 27.2° are attributed to the (110) and (002) crystal planes of graphite carbon nitride. The characteristic peaks at 28.2° and 48.8° correspond to the (222) and (440) crystal planes of BSO, respectively, which are consistent with the standard card of BSO (JCPDSNO:87-0284). In addition, the peaks at 22.5°, 27.2°, 38.0°, 39.6°, 44.5°, 45.9°, 56.1°, 59.4°, 62.1°, 64.7°, 70.6° and 71.9° belong to the (003), (012), (104), (110), (015), (006), (024), (107), (116), (122), (214) and (300) crystal planes of Bi, which are consistent with the standard card of Bi (JCPDS NO: 44-1246). It is worth noting that in the Bi-Bi2Sn2O7 / g-C3N4 composite material, some characteristic peaks of Bi, Bi2Sn2O7 and g-C3N4 appear simultaneously, which indicates that it is a composite composed of Bi, Bi2Sn2O7 and g-C3N4.

[0070] 2. The microstructure of the Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material prepared in Example 1 was analyzed using SEM.

[0071] Figure 2 The SEM images of Bi-Bi2Sn2O7, g-C3N4 and Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic materials prepared in Example 1 are shown in FIG. Figure 2 Middle (A) and Figure 2 (B) are SEM images of different monomers Bi-Bi2Sn2O7 and g-C3N4. It can be seen that B-BSO has nanoparticles of different sizes, with a particle size of about 10nm, showing an aggregated state. Pure g-C3N4 presents a relatively thin nanosheet structure with many wrinkles on the edge, and many large pores are clearly observed. The presence of pores can provide more active sites and the best position for loading. After the Bi-Bi2Sn2O7 / g-C3N4 composite material is formed, g-C3N4 still presents a nanosheet structure with wrinkles on the edge and many large pores and pores on the surface of the sheet. In addition, the surface of the nanosheet is loaded with some Bi-Bi2Sn2O7 nanoparticles with a particle size of 30nm to 200nm. Compared with pure Bi-Bi2Sn2O7, it may have aggregated and agglomerated. This heterojunction constructed between OD / 2D can effectively shorten the charge transmission distance. Thinner sheets and pore structures can enhance the absorption and utilization of light and accelerate the transfer of charges, ultimately enhancing the activity of photocatalytic H2O2 production.

[0072] 3. The photocatalytic H2O2 production performance of the Bi-Bi2Sn2O7 / g-C3N4 composite photocatalyst prepared in Examples 1-3 was analyzed using a liquid ultraviolet spectrometer (UV-1800PC).

[0073] Figure 3The photocatalytic H2O2 production performance of Bi-Bi2Sn2O7, g-C3N4 and Bi-Bi2Sn2O7 / g-C3N4-X (X=1,2,3) nanomaterials prepared in Example 1. Specifically, the activity of the prepared photocatalyst to produce H2O2 was evaluated by 30 minutes of O2 exposure using saturated deionized water at normal pressure and room temperature under visible light and simulated solar radiation conditions. The specific experimental conditions are that the photocatalytic reaction is carried out in a gas-closed system and the reactor is made of quartz. The photocatalytic instrument used is the Labsolar-6a all-glass automatic online trace gas analysis system of Beijing Perfect Light Technology Co., Ltd. The light source is a 300W xenon lamp, in which a filter with a wavelength of (420nm<λ<780nm) and an AnalogueSunlight AM1.5G filter are used respectively. In a typical experiment, Bi-Bi2Sn2O7 / g-C3N4-2 (0.1 g) was added to the photoreactor, followed by 10 mL of C2H5OH and 190 mL of deionized water, followed by ultrasonic stirring for 10 minutes and mixing. Then, oxygen was introduced into the suspension for 30 minutes. After the gas-closed system was evacuated, the suspension was irradiated. In addition, the evolution rate of H2O2 was measured after 5 hours of irradiation under different monochromatic light sources. The catalyst was separated by centrifugal filtration, and 2 mL of 100 mM potassium iodide + 25 μL of ammonium molybdate (20 mM) was added to 20 mL of the supernatant, stirred for 5 minutes, and then the iodine absorbance at 352 nm was detected by UV-visible spectroscopy. The pure Bi-Bi2Sn2O7 sample produced negligible H2O2 after 5 hours of simulated sunlight / visible light irradiation. In addition, under simulated sunlight and visible light irradiation, the total amount of H2O2 produced by the pure g-C3N4 photocatalyst within 5 h was 127.0 μmol L -1 and 91.5 μmol L -1 The average rate was 25.4 μmol L -1 h -1 and 18.3 μmol L -1 h -1 , showing lower activity, which is attributed to the easy recombination of carriers generated by photoexcitation of pure g-C3N4. When the Bi-Bi2Sn2O7 / g-C3N4-X composite material is formed, the photocatalytic activity shows a volcanic trend, and the activity of Bi-Bi2Sn2O7 / g-C3N4-2 reaches the best. Under visible light and simulated sunlight irradiation, the total amount of H2O2 produced by Bi-Bi2Sn2O7 / g-C3N4-2 photocatalyst within 5 hours is 955.5μmol L -1 and 780.5 μmol L -1 The average rate was 191.1 μmol L -1 h -1and 156.1 μmol L -1 h -1 , which are 7.5 and 8.5 times that of pure g-C3N4, respectively, showing excellent photocatalytic H2O2 production activity.

[0074] like Figures 4 to 6 As shown, in order to study the effects of various atmospheres on the photocatalytic production of H2O2, experiments on the photocatalytic production of H2O2 by Bi-Bi2Sn2O7, g-C3N4 and Bi-Bi2Sn2O7 / g-C3N4 were carried out under saturated O2, N2 and air conditions, respectively. Under simulated sunlight conditions, the photocatalytic activities of Bi-Bi2Sn2O7, g-C3N4 and Bi-Bi2Sn2O7 / g-C3N4 all exceeded the photocatalytic activity observed under visible light conditions, which may be due to the presence of higher energy ultraviolet rays in simulated sunlight. In addition, in a pure O2 atmosphere, the photocatalytic yield of H2O2 for the three photocatalysts was the highest, indicating that O2 is one of the necessary conditions for the efficient production of H2O2. It is worth noting that O2 in the aqueous solution and the reactor plays a key role in the photocatalytic reaction of H2O2. Specifically, in an air atmosphere, the photocatalytic activity of Bi-Bi2Sn2O7 / g-C3N4 was reduced to 46.8 μmol L -1 h -1 and 31.5 μmol L -1 h -1 This finding suggests that Bi-Bi2Sn2O7 / g-C3N4-2 is able to oxidize oxygen in water and then produce H2O2 through a series of reactions. However, in a N2 atmosphere, the photocatalytic activity of H2O2 production was greatly reduced, with a rate of only 8.2 μmol L -1 h -1 and 5.6 μmol L -1 h -1 This is because there is only a small amount of O2 in the solution. After it is consumed, it is difficult to react further. The photocatalytic activity of pure g-C3N4 in air atmosphere is reduced to 8.9 μmol L -1 h -1 and 6.4 μmol L -1 h -1 This finding suggests that g-C3N4 is also able to oxidize oxygen in water and then produce H2O2 through a series of reactions. However, in a N2 atmosphere, the photocatalytic activity of g-C3N4 in producing H2O2 was greatly reduced, with a rate of only 1.8 μmol L -1 h -1 and 1.32 μmol L -1 h -1In addition, for pure Bi-Bi2Sn2O7, the photocatalytic activity of Bi-Bi2Sn2O7 decreased to 8.3 μmol L -1 h -1 and 5.7 μmol L -1 h -1 This finding suggests that Bi-Bi2Sn2O7 is also able to oxidize oxygen in water and then produce H2O2 through a series of reactions. However, in a N2 atmosphere, the photocatalytic activity of g-C3N4 in producing H2O2 was greatly reduced, with a rate of only 0.2 μmol L -1 h -1 and 0.1 μmol L -1 h -1 . The above results prove that Bi-Bi2Sn2O7 / g-C3N4-2 has the best photocatalytic activity for H2O2 production and is most active in oxygen. More importantly, cyclic stability experiments were carried out under visible light and simulated sunlight to evaluate the stability of Bi-Bi2Sn2O7, g-C3N4, and Bi-Bi2Sn2O7 / g-C3N4 in the photocatalytic production of H2O2. Under simulated sunlight, the average rate of photocatalytic H2O2 production by Bi-Bi2Sn2O7 / g-C3N4-2 reached 191.1 μmol L in the first cycle. - 1 h -1 After five cycles, it stabilized at 175.2 μmol L -1 h -1 , which is 91.7% of the initial cycle yield. In addition, under visible light irradiation, the average rate of photocatalytic H2O2 production by BBi-Bi2Sn2O7 / g-C3N4-2 in the first cycle was 156.1 μmol L -1 h -1 , remained at 143.8 μmol L after five cycles. -1 h -1 The average rate of photocatalytic H2O2 production of pure g-C3N4 under simulated sunlight reached 46.6 μmol L in the first cycle. -1 h -1 After five cycles, it stabilized at 42.3 μmol L -1 h -1 , which is 90.8% of the initial cycle yield. Under visible light irradiation, the average rate of photocatalytic H2O2 production in the first cycle was 31.5 μmol L -1 h -1 , which remained at 27.2 μmol L after five cycles. -1 h -1The average rate of photocatalytic H2O2 production in the first cycle under simulated sunlight was 8.3 μmol L -1 h -1 , which remained at 4.1 μmol L after five cycles. -1 h -1 The average rate of photocatalytic H2O2 production in the first cycle under visible light irradiation was 5.6 μmol L -1 h -1 , which remained at 2.4 μmol L after five cycles. -1 h -1 The rate is 42.8% of the first cycle performance. Therefore, according to the above analysis, Bi-Bi2Sn2O7 / g-C3N4-2 not only has high photocatalytic H2O2 production activity, but also exhibits excellent cycle durability, so it is expected to become one of the candidate photocatalysts for generating H2O2, such as Figures 7 to 9 shown.

[0075] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material, characterized in that: The following steps are involved: 1) mixing melamine, cyanuric acid and water, and then drying and calcining in sequence to obtain a g-C3N4 photocatalytic material; 2) dispersing the g-C3N4 photocatalytic material obtained in step 1) in water to obtain a photocatalytic material solution; Mixing bismuth nitrate, polyvinyl pyrrolidone and D-mannitol solution to obtain a bismuth nitrate-containing solution; 3) The photocatalytic material solution obtained in step 2), the bismuth nitrate solution and the potassium selenate solution are mixed, the pH value is adjusted to 10.0-12.0, and then a hydrothermal reaction is carried out. After drying, a Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material is obtained.

2. The preparation method according to claim 1, characterized in that: In the step 1), the mass ratio of melamine, cyanuric acid and water is 1:1:

40.

3. The preparation method according to claim 1, characterized in that: The drying conditions in step 1) include: temperature of 60° C. and time of 12 h; The calcination conditions include: heating to 500-600° C. at a heating rate of 5-10° C. / min and keeping the temperature for 1-3 hours.

4. The preparation method according to claim 1, characterized in that: In the step 2), the mass ratio of the g-C3N4 photocatalytic material to water is 1 to 3:

20.

5. The preparation method according to claim 1, characterized in that: In the step 2), the volume ratio of the mass of bismuth nitrate, the mass of polyvinyl pyrrolidone and the D-mannitol solution is 0.48 g:0.4 g:30 mL; The concentration of the D-mannitol solution is 0.5 mol / L.

6. The preparation method according to claim 1, characterized in that: In step 3), the volume ratio of the photocatalytic material solution, the bismuth nitrate-containing solution and the potassium selenate solution is 4:6:1; The concentration of the potassium selenate solution is 0.06 g / mL.

7. The preparation method according to claim 1, characterized in that: The conditions of the hydrothermal reaction in step 3) include: a temperature of 160 to 200° C. and a time of 12 to 24 hours; The drying temperature is 80°C.

8. A Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the Bi-Bi2Sn2O7 / g-C3N4 composite photocatalytic material according to claim 8 in photocatalytic production of H2O2.

10. The use according to claim 9, characterized in that: The application includes: photocatalytic production of H2O2 under visible light or sunlight.

Citation Information

Patent Citations

  • Preparation method of tubular g-C&lt;3&gt;N&lt;4&gt; with visible-light response function

    CN110697667A

  • Composite catalyst capable of efficiently producing hydrogen peroxide and preparation method thereof

    CN113171791A

  • 3D porous carbon nitride composite oxygen-deficient indium oxide Z-type catalyst, and preparation method and nitrogen fixation application of 3D porous carbon nitride composite oxygen-deficient indium oxide Z-type catalyst

    CN114939405A

  • Modified graphite phase carbon nitride photocatalyst as well as preparation method and application thereof

    CN116726969A

  • Porous nano flaky carbon nitride catalyst as well as preparation method and application thereof

    CN117550568A